2008
DOI: 10.1002/ca.20734
|View full text |Cite
|
Sign up to set email alerts
|

The course and variations of the branches of the musculocutaneous nerve in human fetuses

Abstract: The course and branches of the musculocutaneous nerve (MCN) were dissected in 140 human fetal arms. The MCN entered the superior, middle, and inferior part of coracobrachialis in 43%, 37%, and 17% of arms, respectively, and the remaining 3% did not pierce coracobrachialis. The motor branches to biceps were classified as follows: Type 1 (83.6%): a single branch that bifurcated to supply the two heads of biceps; Type 2 (14.3%): two separate branches each innervating one head of biceps; Type 3 (2.1%): a single br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 12 publications
0
27
1
Order By: Relevance
“…The studies and the reported percentages of the specimens, which the MCN did not pierce coracobrachialis, are as follows: Eglseder and Goldman (1997) 29.6%, Choi et al (2002) Ozturk et al (2005) reported that in all 42 extremities, the MCN had no variations, originated from the lateral cord of the brachial plexus and entered the coracobrachialis. Uysal et al (2009) reported that the MCN entered the superior part of coracobrachialis in 43% of specimens, the middle part in 37%, and the inferior part in 17%. In our study, in 65% of arms, the MCN entered from the proximal 1/3 part of coracobrachialis, in 25% of arms, it entered the middle 1/3 part and no sample that the MCN enter distal 1/3 part of coracobrachialis, and in the remaining 10% of the arms, the MCN did not enter coracobrachialis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The studies and the reported percentages of the specimens, which the MCN did not pierce coracobrachialis, are as follows: Eglseder and Goldman (1997) 29.6%, Choi et al (2002) Ozturk et al (2005) reported that in all 42 extremities, the MCN had no variations, originated from the lateral cord of the brachial plexus and entered the coracobrachialis. Uysal et al (2009) reported that the MCN entered the superior part of coracobrachialis in 43% of specimens, the middle part in 37%, and the inferior part in 17%. In our study, in 65% of arms, the MCN entered from the proximal 1/3 part of coracobrachialis, in 25% of arms, it entered the middle 1/3 part and no sample that the MCN enter distal 1/3 part of coracobrachialis, and in the remaining 10% of the arms, the MCN did not enter coracobrachialis.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are only a few studies on the MCN in fetuses (Linell, 1921;KwolczakMcGrath et al, 2008;Guerri-Guttenberg and Ingolotti, 2009;Uysal et al, 2009). As Kwolczak-McGrath et al (2008) emphasized that the body proportions of newborns and infants are rather similar to a fetus than an adult, studying the course of the MCN and the exit points of the motor branches for biceps brachii and brachialis in fetuses will be helpful for clinicians and surgeons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently reported variants include the presence of communicating branches with the median nerve, the nerve not perforating the coracobrachialis muscle (CB) and less frequently its absence (Sunderland, 1978;Krishnamurthy et al, 2007;Uysal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, Kawashima et al (2007) later ruled out this cause-effect relationship in orangutans. The musculocutaneous nerve penetrates the coracobrachialis muscle in fetuses (not embryos), although the nerve component was not considered (KwolczakMcGrath et al 2008;Uysal et al 2009;Kervancioglu et al 2011). In addition, the characteristic topographical relationship between a muscle and the muscle-penetrating nerve is also known for the piriformis muscle and the peroneal nerve component of the sciatic nerve, for which segmental variations have been described in detail by Chiba and colleagues (Chiba, 1992;Chiba et al 1994).…”
Section: Discussionmentioning
confidence: 99%